VO#52: Approval of unit rates of non-schedule item for supplying, fabrication & installation of steel frames for RCC steps of gallery in auditorium structure - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the approval of unit rates of non-schedule item for supplying, fabrication & installation of steel frames for RCC steps of gallery in auditorium structure of BRACU new campus building.